Case report: Gene mutation analysis and skin imaging of isolated café-au-lait macules - Zhong, Zhenyu; Yang, Tianhui; Liu, Siqi; Wang, Shan; Zhou, Shan; Du, Shuli; Zheng, Liyun; Wang, Xiuli; Wang, Hui; Wang, Yifan; Gao, Min (Frontiers in Genetics, 2023)
Background: Cafe´-au-lait macules (CALMs) are common birthmarks associated with several genetic syndromes, such as neurofibromatosis type 1 (NF1). Isolated CALMs are defined as multiple café-au-lait macules in patients without any other sign of NF1. Typical CALMs can have predictive significance for NF1, and non-invasive techniques can provide more accurate results for judging whether café-au-lait spots are typical. This is the first time that skin images of CALMs were recorded. Objectives: The study aimed to investigate gene mutations in six Chinese Han pedigrees of isolated CALMs and summarize the characteristics of CALMs under dermoscopy and reflectance confocal microscopy (RCM). Methods: In this study, we used one-generation sequencing to test for genetic mutations in six families and second-generation sequencing in two families. We used dermoscopy and RCM to describe the imaging characteristics of CALMs. Results: In this study, we tested six families for genetic mutations, and two mutations were identified as novel mutations. The first family had a new heterozygous mutation (NM_001042492.2;c.7355G>A), which encodes R2452H (p.Arg2452His). The second family had a novel frameshift mutation (NM_001042492.2; c.2739_2740delAC), which encodes I913Mfs*5. According to genotype-phenotypic correlation analyses, proband with frameshift mutation tended to have a larger number of CALMs and a higher rate of having atypical CALMs. Dermoscopy showed uniform and consistent tan-pigmented network patches with poorly defined margins with a lighter color around the hair follicles. Under RCM, the appearance of NF1 comprised the increased pigment granules in the basal layer and significantly increased refraction. Conclusion: A new heterozygous mutation gene and a new frameshift mutation of NF1 were reported. This article explained the properties of dermoscopy and RCM with CALMs.